" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
-5x+2x=-8 -10
-3x=18 :/3
x= 6
2) 7x+14=5x-22
7x-5x=-22-14
2x=-36 :/2
x=-18
3) -3+2x-6=3-4x
2x+4x=3+3+6
6x=12 :/6
x=2
4) 2(x-3)+3(4-x)=5
2x-12+12-3x=5
2x-3x=5-12+12 (-12+12=0)
-x=5 :/(-1)
x=-5
5) 2(x+4)-5(x+3)=2
2x+8-5x-15=2
2x-5x=2-8+15
-3x=9 :/(-3)
x=-3
6) 3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
3x-4x=-4+12-10
-x=-2 :/(-1)
x=2
7) -2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
-2x+8x=-6+6-12 (-6+6=0)
6x=-12 :/6
x=-2
8) (3-2x)-(x+4)-(2x-5)=(3x-4)-(5x+7)
3-2x-x-4-2x+5=3x-4+5x-7
-2x-x-2x-3x-5x=-4-7-3+4-5
-3x=-15 :/(-3)
x=5
9) -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
+2x-2x-3x-2x-3x=-1-5-7+4+4
-8x=-5 :/(-8)
x=0,6(3)
10) 2(x-7)-(x+2)=4(x+3)+2(x-9)
2x-14-x-2=4x+12+2x-18
2x-x-4x-2x=+12-18+14+2
-5x=10 :/(-5)
x=-2
11) -3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=-8+72+18+48
-26x=130 :/(-26)
x=-5
12) 4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
5x+x-2x=-3-4+15
4x=8 :/4
x=2
-3x = -18
x = 6
2) 7x+14 = 5x -22
2x = -36
x= -18
3) -3 + 2x - 6 = 3 - 4x
-12 =-6x
x = 2
4) 2(x - 3) + 3(4 - x) = 5
2x -6 + 12 -3x =5
-x = -1
x = 1
5) 2(x + 4) - 5(x + 3) = 2
2x +8 - 5x +10 = 2
-3x = -16
x = 5,(3)
6) 3(x - 4) - 2(2x - 5) = -4
3x - 12 - 4x + 10 = -4
-x = -2
x = 2
7) -2(x + 3) + 4(2x +3) = -6
-2x -6 +8x +12 = -6
6x = -12
x= -2
8) (3 - 2x) - (x + 4) - (2x + 5) = (3x - 4) - (5x + 7)
3 -2x -x -4 - 2x -5 = 3x - 4 - 5x -7
-5x +2x = -11 +6
- 3x = -5
x = 3/5
9) - (4 - 2x) - (2x + 4) = (3x - 1) +(2x - 5) - (7 - 3x)
-4 +2x - 2x -4 = 3x -1 +2x -5 -7 +3x
-8x = -5
x = 1,25
10) 2(x - 7) - (x + 2) = 4(x + 3) + 2(x - 9)
2x -14 -x -2 = 4x +12 +2x -18
-5x = 10
x = -2
11) -3(x +6) - 6(2x + 8) = -2(4 - x) + 9(x + 8)
-3x -18 -12x -48 = -8 +2x +9x +72
-15x -11x = 64 + 66
-26x = 130
x = -5
12) 4 - 5(3 - x) = -x - (3 - 2x)
4 -15 +5x = -x -3 +2x
4x = 8
x =2